2022
DOI: 10.1177/00469580221082781
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Outpatients’ Knowledge, Attitude, and Practice Toward Managing Diabetes in Saudi Arabia

Abstract: Introduction: When it comes to non-communicable diseases like diabetes, inadequate knowledge, attitude, and practice are often linked to poor health outcomes. This study aims to assess the patients’ knowledge, attitude, and practice (KAP) of diabetes in the outpatient department of a university teaching hospital in Saudi Arabia. Methodology: In this cross-sectional study, diabetes type 2 patients attending outpatient departments at a university teaching hospital, Riyadh, were assessed regarding their knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…This is clearly seen in the KAP questionnaire results of urban population where 76% have good knowledge of which 63% have good attitude and 65% have good practice towards treatment and prevention of the disease as compared to the rural population where 39%, have knowledge of disease, 37% had good attitude of which 31% have good practice regarding the disease. Similar results were seen in studies by Nithin et al [10] , Wael et al [11] , Sen et al [12] showing the presence of good knowledge to be a factor of good practices and attitude towards the disease. Most of the rural population was unaware of diabetes and its significance on the eyes.…”
Section: Discussionsupporting
confidence: 88%
“…This is clearly seen in the KAP questionnaire results of urban population where 76% have good knowledge of which 63% have good attitude and 65% have good practice towards treatment and prevention of the disease as compared to the rural population where 39%, have knowledge of disease, 37% had good attitude of which 31% have good practice regarding the disease. Similar results were seen in studies by Nithin et al [10] , Wael et al [11] , Sen et al [12] showing the presence of good knowledge to be a factor of good practices and attitude towards the disease. Most of the rural population was unaware of diabetes and its significance on the eyes.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have obtained different results regarding knowledge of T2DM. The average knowledge score for DM was good among the participants in Mansy et al's [ 24 ] and Zibran et al’s [ 25 ] studies. Conversely, in India, Srinivasan et al [ 26 ] showed that 58% of their participants lacked adequate knowledge of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research [26], regular exercise improves fasting blood glucose, plasma insulin levels, glycemic control, and insulin resistance. Badedi et al [27], Al-Aboudi et al [28], and Ismail et al [29] investigated diabetes knowledge and behaviour in three different contexts.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…In three studies [13,15,18], patients' understanding of the importance of controlling blood sugar levels and making lifestyle changes to reduce the incidence of diabetes complexity was painfully low. Patients' levels of education may influence the specificity of diabetic complications they may experience [27][28][29].…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%